An Imaging Stewardship Initiative to Reduce Low-Value Positron Emission Tomography-Computed Tomography Use in Hospitalized Patients. Issue 6 (November 2020) - Elias, Richard M.; Kashiwagi, Deanne; Lau, Christopher; Hansel, Stephanie L.
Abstract : ABSTRACT: This quality improvement initiative was aimed at reducing low-value Positron emission tomography-computed tomography (PET-CT) studies performed on hospital inpatients. Requests for PET-CT with a predetermined low-value indication triggered a requirement for the ordering provider to call the Nuclear Medicine radiologist to discuss the case for approval of the testing. A retrospective review of inpatient PET-CT approximately 2 years immediately before and after the implementation revealed a 20.6% decrease in scans for low-value indications after the intervention, from 0.397 to 0.315 studies per day ( p < .05; CI −0.158 to −0.005). The overall daily rate of PET-CT was reduced by 23%. Of the 12 low-value indications, 7 had reduced volumes (aggregate 43 fewer scans), 1 was unchanged, and 4 showed an increase in volumes (aggregate of 10 additional scans). Several common indications for inpatient PET-CT that were not targeted for reduction by this intervention also demonstrated large decreases in volumes during the intervention.